Research progress in the preparation and application of h-BN containing ceramics - Xusheng LIU; Xuekun TIAN; Zhenyi ZHAO; Donghong YAN; Tianpei YIN; Jinhua LIU; Xinmei HOU; Xinhong LIU (工程科学学报, 2025)
The development and application of hexagonal boron nitride (h-BN) ceramics are central to materials science research. As a wide-bandgap insulator, h-BN offers a range of exceptional properties, including a high specific surface area, excellent thermal conductivity, superior mechanical strength, thermal shock resistance, chemical inertness, and dielectric transparency. Notably, monolayer single-crystal h-BN outperforms graphene in fracture toughness, with an effective energy release rate an order of magnitude higher. Furthermore, atomically h-BN demonstrates wettability transparency similar to that of graphene, enhancing its functional versatility. These remarkable attributes have led to the widespread application of h-BN ceramics in both traditional and advanced fields. In established industries, h-BN ceramics are essential components in continuous casting separating rings, side sealing plates for thin-strip continuous casting, crucibles, sealing rings for gas sensors, high-temperature furnace parts, and vacuum coating evaporation boats. In emerging technologies, h-BN ceramics are gaining attraction in electronics, aerospace, coatings, 3D printing, and biomedicine, demonstrating the significant potential for future advancements. The fabrication of h-BN ceramics mainly relies on sintering, a critical final step in ceramic production that determines the ultimate performance of materials. However, the intrinsic properties of h-BN—characterized by strong covalent bonding, a high melting point, and a low solid-phase self-diffusion coefficient—present substantial challenges in achieving high-density sintered bodies. As a result, pure h-BN ceramics often suffer from low sintering activity and insufficient mechanical properties. Addressing these challenges has become a key research focus, with efforts directed at incorporating sintering aids, introducing secondary or tertiary phases to form composites, refining sintering processes, and optimizing sintering aids to improve densification. Various sintering techniques have been employed to produce h-BN ceramics, including hot pressing, pressureless sintering, hot isostatic pressing, spark plasma sintering, oscillatory sintering, and microwave sintering. This review explores the preparation methods and application landscape of h-BN-based ceramics, with a particular emphasis on their sintering processes. It also highlights the vast potential of h-BN ceramics and their composites to drive innovation across a wide range of industrial sectors. Future research on h-BN ceramic materials should focus on the following priorities: Given the flaky morphology of h-BN and its relatively large grain size, which complicate the sintering of h-BN-based ceramics, it is crucial to explore nanostructured h-BN ceramics with diverse morphologies. Efforts should aim to optimize sintering processes and reduce time requirements while emphasizing critical role of h-BN in next-generation high-performance materials. Advancing techniques, improving sintering aids, and engineering multiphase ceramic materials will help facilitate precise microstructural control. This, in turn, will further enhance the mechanical, thermal, and dielectric properties, paving the way for materials with optimized overall performance. Despite significant progress, key challenges remain unresolved. The lack of a scalable method for producing high-purity, high-quality h-BN ceramics continues to hinder their widespread adoption. Overcoming this bottleneck would revolutionize the development of ceramic composites with improved mechanical strength and thermal conductivity, unlocking new opportunities across various applications. These insights can inspire researchers and professionals, providing a theoretical foundation and practical guidance for future innovations in the h-BN ceramics field.